THE FUNCTIONS OF DIRECTIVE SPEECH ACTS OF MALEFICENT CHARACTER IN MALEFICENT MOVIE - Biatrik, Desy; Natsir, M.; Kuncara, Singgih Daru (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
ABSTRACT The objectives of this study were to identify the types of directive speech acts and functions of language existed in Maleficent’s utterances. There were two theories used in order to fulfill the two objectives of this study. Searle’s (1979) types of directives helped the writer to identify types of directives speech acts uttered by Maleficent. While Jakobson’s (1960) functions of language helped to identify functions of language existed in each directive of Maleficent. This study was a qualitative research due to the fact of using words as its data taken from Maleficent movie script. As the method in analysing data, this study used conversation analysis in which taking account not only the utterances of Maleficent, but also the actions involved within. As the results, there were five types of directive speech acts and three functions of language found in the utterances of Maleficent in Maleficent movie script. The five types of directive speech acts were commanding, inviting, forbidding, requesting, and suggesting. Of all these five types, commanding was the most uttered and effective type by Maleficent regarding her role as the Moors’ protector who gave her the authority to command other people. Meanwhile, the three functions of language in Maleficent’s directives were expressive, conative, and referential.